Human interface and the management of information. 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, proceedings /: 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, proceedings. Information and knowledge design : Part I, (2015) - Unknown
No abstract available